BIAS BETA DAN MODEL KOREKSI - Aulia Hanani; Endang Emawati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
The purpose of this study is to analyze the existence of bias in beta values in the Jakarta Stock Exchange (JSX) that is a developing capital market and have a significant number of stocks that illiquid. Therefore, the measurement of beta is likely bias. The existence of bias beta values is caused by nonsynchronous trading. This study replicates the previous study from Hartono and Surianto (2000). It uses 88 samples of listing firms in the JSX from January 1997 until March 2002. The hypothesis testing concludes that during the-interval period beta values in the JSX are bias. The bias of beta values can be corrected with Scholes-Williams model, Dimson model, and Fowler-Rorke model. The Fowler-Rorke model gives the best result to reduce the bias than others.